7d+6=42

Simple and best practice solution for 7d+6=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7d+6=42 equation:


Simplifying
7d + 6 = 42

Reorder the terms:
6 + 7d = 42

Solving
6 + 7d = 42

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 7d = 42 + -6

Combine like terms: 6 + -6 = 0
0 + 7d = 42 + -6
7d = 42 + -6

Combine like terms: 42 + -6 = 36
7d = 36

Divide each side by '7'.
d = 5.142857143

Simplifying
d = 5.142857143

See similar equations:

| 4t-6=2t+18 | | (5u+3)(5+u)=0 | | -3/9P=-2 | | 8-12(sin^2)x=4(cos^2)x | | -(w+5)+2w-11=-27 | | 4z+2z=5z-3 | | d(t)=360-60t | | 7y+15=4y-6 | | x^2+y^2-8x+2y+8=0 | | 2n-3(5)=n-2(7) | | 2n-3(5)=7(n-2) | | 6(X-4)=32-2x | | 4*1/2−2*2/3= | | -4/3s=7/9 | | 5x-1.5=9c+3 | | 4z-9z=32 | | 30.25+x=35 | | 4x1/2−2x2/3= | | 2x(3)=5(x-1) | | 3(z+8)-2z=23 | | 8x+4=11x+10 | | 3x+5.39=-4.58 | | (-3x^3/y^2)^2 | | x-10x-1=0 | | 9-4x=-5x+5 | | 8d=9d-18 | | 7x=2+3x+6x | | 4t+8=68 | | -4.1+8.4=9s-5.3-8s | | 11-2x+12=15 | | 7n=2+3x+6x | | 9.6=17s |

Equations solver categories